Manajemen Pemuatan Penumpang Dan Kendaraan Terhadap Keselamatan Kapal Roro - Eni Tri Wahyuni (Majalah Ilmiah Bahari Jogja, 2020)
This study aims to learn the methods and strategies in the correct loading procedure when loading based on operating standards applied at the port, learn how operational work in the field, anything that deviates from loading procedures, trying to improve safety. The method used is a normative legal method or normative jurisdiction. Specifications Analysis of the data used is qualitative of primary data through interviews and observations and secondary data in assessments and books relating to this research. Based on the research it can be concluded about the management of loading and vehicles for safety, with loading financial management in accordance with loading procedures and operational management in the field in accordance with no problems in recording manifests that are inaccurate mismatches between procedures and the implementation of loading activities. recording of non-accurate manifests to be allowed in the field according to ship loading hours, so that from this ticket we can get data that matches the manifest, so that later it is needed, manifest data can provide clear and correct information about loading what is being transported. And loading can proceed according to existing loading procedures for safety.